Avaliação da qualidade dos serviços de uma biblioteca universitária na percepção dos discentes - Soares, Djeanne Batista Costa (2024)
The search for excellence in service quality is growing in organizations, with an expanded focus that encompasses both products and service provision. University libraries, as service providers, are essential for researchers and students, offering information for teaching, research and extension. From the perspective of service quality, there was a need to evaluate and understand users' perception of the quality of services offered by university libraries. Indeed, the general objective of this study is to evaluate the perception of UFC Sobral student users regarding the quality of services offered by the Libraries of the Federal University of Ceará, Sobral Campus. The aspects analyzed include the quality of the collection, physical facilities, employee service and the use of online services. The SERVPERF metric, an adaptation of the SERVQUAL metric, was used to analyze the quality dimensions. The methodology used was exploratory-descriptive with a qualitative-quantitative approach, based on a case study, data were collected through an electronic questionnaire, sent to students at the UFC Campus in Sobral. The survey covered 134 students out of 2,560 undergraduate and postgraduate students, representing a return of 5.23% of students. It is expected that the results will contribute to the improvement of services and the promotion of an environment conducive to research in the academic community, providing advances in the field of quality of services in university libraries.